Memory B Cells Induced by Sputnik V Vaccination Produce SARS-CoV-2 Neutralizing Antibodies Upon Ex Vivo Restimulation - Byazrova, Maria G.; Kulemzin, Sergey V.; Astakhova, Ekaterina A.; Belovezhets, Tatyana N.; Efimov, Grigory A.; Chikaev, Anton N.; Kolotygin, Ilya O.; Gorchakov, Andrey A.; Taranin, Alexander V.; Filatov, Alexander V. (Frontiers in Immunology, 2022)
The development of safe and effective vaccines against SARS-CoV-2 remains a global health priority. To date, several million people have been vaccinated with Sputnik across the globe, yet the protective properties of this vaccine continue to be widely debated, as the information available has been somewhat mixed. Here, we present a comprehensive analysis of B cell immunity elicited by Sputnik vaccination. Based on our measurements of more than a dozen of various parameters across 4 different timepoints, we conclude that the memory B cells induced by Sputnik V vaccination, both in their numbers and productivity, are comparable to those produced during the natural infection. Similar to reports examining responses to other SARS-CoV-2 vaccines, we show that Sputnik-vaccinated individuals with a prior history of SARS-CoV-2 infection mount a stronger B cell response than the naïve individuals. Conducted independently of the Sputnik developers or manufacturers, our study goes beyond the simple measurements of neutralizing antibody responses in the vaccinees, and provides an important outlook into future recall responses by memory B cells upon their encounter with the virus, including the viral variants of concern. We believe that our data will be instrumental for decision-making authorities in light of the emerging viral variants.